Maritime social and economic developments in Southeast Asia - Hanizah Idris; Tan, Wan Hin; Mohammad Raduan Mohd Ariff (Monograph series (Universiti Malaya. Institute of Ocean and Earth Sciences), 2008)
This book brings together the past and the future of maritime social and economic development in the region. The various authors identify current as well as past trends in maritime social and economic developments that have propelled the region to being one of the most dynamic expanses in the world and explore certain key issues. It is the hope that this book will serve as resource material to scholars and researchers interested in the maritime issues of Southeast Asia.